Effects of virtual reality environments on overground walking in people with Parkinson disease and freezing of gait. (3rd April 2023) - Yamagami, Momona; Imsdahl, Sheri; Lindgren, Kyle; Bellatin, Olivia; Nhan, Nawat; Burden, Samuel A.; Pradhan, Sujata; Kelly, Valerie E.
Abstract: Background: Freezing of gait (FoG) is a common target of rehabilitative interventions for people with Parkinson disease (PD). Virtual reality (VR) holds potential for advancing research and clinical management of FoG through flexible creation of FoG-provoking environments that are not easily or safely replicated in the clinic. Objective: The aim of this study was to investigate whether VR environments that replicate FoG-provoking situations would exacerbate gait impairments associated with FoG compared to unobstructed VR and physical laboratory environments. Methods: Gait characteristics (pace, rhythm, variability, asymmetry, and postural control domains) and festination were measured using motion capture while people with PD walked in VR environments based on FoG-provoking situations (doorway, hallway, and crowd environments) compared to unobstructed VR and physical laboratory environments. The effect of VR environments was assessed using one-way repeated measures ANOVAs with planned contrasts. Results: Ten participants (mean age 74.1 years, 3 females, Hoehn and Yahr stage 2–3) with PD who self-reported FoG participated. Gait speed and step length were reduced in all VR environments compared to the physical laboratory. Step width was wider, step length was more variable, and festination was more common for some of the VR environments compared to the physical laboratory environment. Compared to the unobstructed virtual laboratory environment, step length was more variable in VR crowd and doorway environments. Conclusions: The exacerbation of gait impairments that are characteristic precursors of FoG in FoG-provoking VR environments supports the potential utility of VR technology in the assessment and treatment of gait impairments in PD. Implications for rehabilitation: Freezing increases fall risk and reduces quality of life in Parkinson disease (PD). Virtual reality (VR) can simulate visuospatial environments that provoke freezing. Immersive VR doorway, hallway, and crowd environments were developed. Gait speed slowed when people with PD walked overground in all VR environments. Step variability and festination increased in freeze-provoking environments.